2015
DOI: 10.7307/ptt.v27i3.1547
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Extra Buses Scheduling Strategy in Public Transport

Abstract: This paper presents a dynamic extra buses scheduling strategy to improve the transit service of transit routes. In this strategy, in order to decide when to dispatch an extra bus, the service reliability of transit route is assessed firstly. A model aimed at maximizing the benefit of the extra buses scheduling strategy is constructed to determine how many stops extra buses need to skip from the terminal to accommodate passengers at the following stops. A heuristic algorithm is defined and implemented to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…An RCC is used to balance arriving and taking-off. RCC is a dynamic ratio of the total number of arrivals to the total number departures at a moment, which can be defined using equation (13) t…”
Section: Guidance Decision Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…An RCC is used to balance arriving and taking-off. RCC is a dynamic ratio of the total number of arrivals to the total number departures at a moment, which can be defined using equation (13) t…”
Section: Guidance Decision Factorsmentioning
confidence: 99%
“…They conclude that the time-based strategy is better than the deficit-based strategy and the bilevel model proposed performs well with regard to the objective of reducing travel time costs. [13][14][15][16][17][18][19] Wei et al 20 studied the impact of different guidance information on traffic flow with different traffic volumes and different induction rates. Khanjary et al 21 elaborated an autonomous combined traffic signal controller and route guidance system, and their simulation results showed that the system improved the average speed of vehicles significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Bie et al [ 18 ] developed a new algorithm based on GPS data to partition bus operating hours into time of day intervals. Yu et al [ 19 ] used the variation of the intervals between a vehicle and its following vehicle to estimate the irregularity of transit operation and consequently presented a dynamic extra buses scheduling strategy.…”
Section: Introductionmentioning
confidence: 99%